A Comparative Study of Student Learning Outcomes in Geography Learning Using ArcGIS Application and QGIS Application - Stella Carolline Aurellia; Budiman Tampubolon; Putri Tipa Anasi (Yayasan Keluarga Guru Mandiri, 2023)
One of the characteristics of learning geography in the 21st century is that teachers must strive to develop technology that supports learning. This study aims to discover differences in learning outcomes in geography learning using the ArcGIS application and the Quantum GIS application for senior high school students. The method used was a quantitative experiment with a quasi-experimental form. Determination of the sample by purposive sampling consisted of two experimental classes, with each class totaling 34 students. Students' learning outcomes were tested with a two parties t-test which previously tested data normality, data homogeneity, and the hypothesis. The results of this study show that the experimental class using the ArcGIS application has a post-test average score of 83.03 and the class using the Quantum GIS application has a post-test average score of 77.50. Therefore, there are differences in the learning outcomes of the two experimental classes, which show that using the ArcGIS application is more effective in geography learning in senior high schools than the Quantum GIS application. The results of this study can be used as material for consideration of implementing the use of innovative learning media and improving mapping skills for high school students.